Properties of Pickering Stabilized Associative Water‐In‐Water Emulsions Based on Ultra‐High Molecular Weight Polyacrylamides - Rafael B. Lira; Alexander Plucinski; YouBeen Ko; Niamh Bayliss; Chris vanEwijk; Wouter H. Roos; Bernhard V. K. J. Schmidt (Advanced Materials Interfaces)
Abstract Completely water‐based multicompartment systems have attracted a broad interest in recent years, mainly due to their versatile features such as permeability. Here, the associative formation of water‐in‐water (w/w) emulsions based on ultra‐high molecular weight poly(N,N‐dimethylacrylamide) (PDMA) and poly(4‐acryloylmorpholine) (PAM) is studied. The system is investigated using a combination of fluorescence microscopy and spectroscopy techniques. The system phase‐separates into aqueous droplets at very low polymer concentrations and exhibits intriguing physical properties. The formed emulsion droplets are extremely fluid (5–10 mPa.s), enable fast (5 µm2 s−1), nearly complete (mobile fraction ≈0.8) and unhindered diffusion within and across compartments, which is a hallmark of fluids. Furthermore, the very low interfacial tension (0.18–0.40 mN m−1) enables droplet coalescence leading to equilibrium formation of various emulsion structures. These properties show similarities to cell cytoplasm and coacervates and hence this type of w/w emulsion formed via associative non‐ionic interactions is a new direction in the field of synthetic cells and synthetic biology.